The Pharmaceutical Technology Approach on Imaging Innovations from Italian Research - Giorgia Ailuno; Rosa Maria Iacobazzi; Antonio Lopalco; Sara Baldassari; Ilaria Arduino; Amalia Azzariti; Sara Pastorino; Gabriele Caviglioli; Nunzio Denora (MDPI AG, 2021)
Many modern therapeutic approaches are based on precise diagnostic evidence, where imaging procedures play an essential role. To date, in the diagnostic field, a plethora of agents have been investigated to increase the selectivity and sensitivity of diagnosis. However, the most common drawbacks of conventional imaging agents reside in their non-specificity, short imaging time, instability, and toxicity. Moreover, routinely used diagnostic agents have low molecular weights and consequently a rapid clearance and renal excretion, and this represents a limitation if long-lasting imaging analyses are to be conducted. Thus, the development of new agents for in vivo diagnostics requires not only a deep knowledge of the physical principles of the imaging techniques and of the physiopathological aspects of the disease but also of the relative pharmaceutical and biopharmaceutical requirements. In this scenario, skills in pharmaceutical technology have become highly indispensable in order to respond to these needs. This review specifically aims to collect examples of newly developed diagnostic agents connoting the importance of an appropriate formulation study for the realization of effective products. Within the context of pharmaceutical technology research in Italy, several groups have developed and patented promising agents for fluorescence and radioactive imaging, the most relevant of which are described hereafter.